Zrównoważony rozwój w jednostkach samorządu terytorialnego - Rogus, Marlena (Sustainable Development of the Local Government Administration, 2006)
The article introduces sustainable development of the local government administration. The first definition sustainable development is presented as development that meets the needs of the present and of future generations to meet their own needs. The sustainable development should be an elementary and inseparable part of the management in local governments administration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 470-478